Closing the phosphorus cycle by recycling lake sediments in agriculture - Kiani, Mina (Helsingin yliopisto, 2023)
Phosphorus (P) is an essential plant macronutrient, originating mainly from non-renewable phosphate rocks. Rock phosphate (phosphorite) is one of the critical raw materials listed by the European Commission. Unsustainable P use affects food and water security and causes serious environmental problems such as the eutrophication (i.e., nutrient enrichment) of lakes. Given the essential role of P recycled from sediment to overlaying water in sustaining eutrophication, the removal of nutrient-rich sediments from lakes is one of the most effective restoration techniques, especially for small shallow lakes. Sediment removal removes P accumulated in lake sediments and offers the opportunity to close the P cycle by using the removed P in a sustainable manner. In the three studies of this thesis, I examined the potential of closing the agricultural P cycle by using lake sediments for crop production. The studies focused on the best practice for sediment recycling based on pot (I) and field experiments (II) along with investigating the changes to lake P dynamics after sediment removal (III). Excavating all the 7500 m3 of sediment from a 1-ha shallow eutrophic Lake Mustijärv (Viljandi, Estonia) was the starting point of this work. During the lake restoration, 6.4 Mg of P was removed, including 2.4 Mg of NaOH-extracted P (Fe−P), one of the major potentially bioavailable P forms. In the next step, various application methods were examined to use large quantities of lake sediments for grass production during a nine-month lysimeter experiment. The heavy metal and organic contaminant contents in the sediment were below the levels that would pose ecological or health risks according to the threshold values set by Ministry of the Environment, Finland. Using the excavated sediment with a low Fe:P mass ratio (6) resulted in a greater plant-availability of P and other nutrients compared with the sandy loam soil from the lake shore. The fertilization effect and the substantial increase in the growth and P uptake of ryegrass in the sediment-based treatments made the sediment application advisable for crop production. Of all the P fractions, the Fe-P fraction contributed most to plant P uptake. From an environmental impact perspective, even if a relatively thick layer of sediment was applied on top of the soil, it did not increase the risk of phosphate and mineral nitrogen (N) leaching. In addition, a biochar layer slightly reduced P and N leaching from the sediment. Furthermore, the environmental effects of various sediment application methods for grass production were studied in a four-year field experiment on the shore of the restored lake. The treatment effects on greenhouse gas (GHG) emissions, N and P leaching, aggregate stability, and soil biota were analyzed. The excavated sediment sustained grass biomass yield of 12 Mg ha−1 in the field, even though yield enhancement was less obvious compared with the lysimeter experiment. In addition to 75 g m−3 of easily soluble P, the sediment had also high contents of other soluble essential plant nutrients, including sulfur (S), calcium (Ca), magnesium (Mg), boron (B), zinc (Zn), and a fair supply of copper (Cu). Also, the sediment continuously provided a moderate supply of N to the plants over the four-year field experiment, which was likely due to mineralization of the organic reserves of the sediment. Considering the environmental impacts, the sediment-based growing media were observed to have higher carbon dioxide (CO2) emissions (579 vs. 400 mg CO2−C m−2 h−1) yet broadly similar nitrous oxide (N2O) emissions compared with the soil surrounding the lake. Also, applying a thick layer of excavated sediment increased the risk of phosphate and mineral N leaching. In addition, sediment treatments had different bacterial and fungal community compositions compared with soil. This could result in different mineralization pathways in soil and sediment-based treatments. During a two-year follow-up period, internal P loading formation in a recently restored lake was examined using sediment and lake water chemistry data. Soon after sediment removal, a high pool of releasable P was rebuilt in the lake due to exceptionally high external P loading. In addition, extensive anoxia of the surface sediments and in the water overlying the lake bottom was revealed. This resulted in high internal P loading, which sustained the eutrophication. Variations in the release rate of P from the newly formed sediments were explained by changes in sediment Fe−P and labile P fractions. Moreover, the gradual decrease in different P forms and organic matter from lake inflow towards outflow revealed the important role of sediment accumulation basins in lake restoration. Sediment from Lake Mustijärv was rich in organic matter and was a good source of several essential nutrients, including P, in plant-available form. I suggest that, instead of using a thick layer of sediments alone as a growing medium, sediment would be applied to soils based on crop nutrient requirements. Such an application, similar to the application of organic fertilizers, may reduce nutrient losses through leaching. With the aim of closing the agricultural P cycle, this case study can be upscaled to other shallow lakes with similar sediment properties.